Mapping women's and gender studies in the academic field in Slovenia - Antić Gaber, Milica (CEPS journal, 2017)
The aim of the present paper is to map the development of women's and gender studies (WGS) in the academic field in Slovenia. Slovenia is the first of the former Yugoslav state republics in which WGS have succeeded in entering the academic field and becoming part of institutionalised university study. In this paper we will ask the following questions: How, when and why did this happen? How was this connected to women's and feminist movements and politics regarding women's issues and demands? What were the obstacles in this process? Who were the agents and what were the factors that supported demands for the incorporation of WGS in academia? How has the field evolved in the last few decades? What were the phases of this development? Which fields were the forerunners, which were the late-comers and which are still left aside? What are the thematic scopes taught in WGS courses? In which degrees are the courses offered and what are their modules? Who teaches them? The mapping in this paper is mainly based on primary sources of university programmes and their curricula at faculties of the University of Ljubljana, as well as on interviews with important agents in the field.
Keywords: spol; sex; visokoošolsko izobraževanje; higher education; gender studies; študije spolov; institutionalization; ženske študije; institucionalizacija; university courses; visokošolsko izobraževanje; Slovenia; univerzitetni programi; Slovenija